2006
DOI: 10.1515/hf.2006.070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of variation in modulus of elasticity on creep of wood during changing process of moisture

Abstract: This study considered the influence of variations in the modulus of elasticity (MOE) on the mechano-sorptive (MS) creep of wood. MOE in the radial direction (E R ) was investigated as a function of changes in moisture content (MC). E R values were lower during both adsorption and desorption processes than under constant MC, despite the same MC values. However, the effects observed were small and are thus not of great practical importance.Keywords: changing process of moisture; mechanosorptive phenomenon; modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…The similar phenomena were also reported when wood was subjected to bending force by Takahashi et al [35], Lu et al [36], and Jiang et al [37]. When water molecules penetrated into the wood cell wall, a slight amount of water induced a bridge effect involving hydrogen bonds forming a relative ordered cohesion state between molecular chains [35]. In the previous studies [14,30,32,38], the moisture ranges were limited, in hence, no local maximum value of E L were reported.…”
Section: Tensile Modulus Esupporting
confidence: 87%
See 1 more Smart Citation
“…The similar phenomena were also reported when wood was subjected to bending force by Takahashi et al [35], Lu et al [36], and Jiang et al [37]. When water molecules penetrated into the wood cell wall, a slight amount of water induced a bridge effect involving hydrogen bonds forming a relative ordered cohesion state between molecular chains [35]. In the previous studies [14,30,32,38], the moisture ranges were limited, in hence, no local maximum value of E L were reported.…”
Section: Tensile Modulus Esupporting
confidence: 87%
“…The local maximum value of E L was 10.7, and 8.4 GPa, respectively for poplar at 2.0% MC and Chinese fir at 2.4% MC. The similar phenomena were also reported when wood was subjected to bending force by Takahashi et al [35], Lu et al [36], and Jiang et al [37]. When water molecules penetrated into the wood cell wall, a slight amount of water induced a bridge effect involving hydrogen bonds forming a relative ordered cohesion state between molecular chains [35].…”
Section: Tensile Modulus Esupporting
confidence: 78%
“…Therefore, the unstable state of wood was caused by changes in MC regardless of the presence of stress bias. When water penetrates the cell wall, moisture molecules not only break and reform the hydrogen bonds, but also provide free volume for the rearrangement of mircofibrils and promote the “rearrangement of the hydrogen bonds” within the polymer network [ 18 , 19 , 20 ]. Samples of VEC, which had been kept under constant condition for a long time, were presumed to be more stable in the course of tensile tests as compared with samples of MSC.…”
Section: Resultsmentioning
confidence: 99%
“…Transient hydrogen bonds form free volume and localized stress in wood cell wall, which disturbs the equilibrium state of the molecular packing mode. Under an external load, the formation of free volume and localized stress accelerates the shear slip between the crystalline and amorphous phases in the cell wall [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing degree of n E ″ was obviously higher than the decreasing degree of n E ′, regardless of the ramping rate. Takahashi et al confirmed that the decrease in elasticity is not as great as the increase in damping during the sorption process [ 32 ]. Since cellulose, hemicellulose, and lignin have different absorbability, the extents of hygro-expansion vary within the wood cell walls, providing the shear slip between cellulose and matrix, and leading to a large energy dissipation [ 21 , 24 ].…”
Section: Resultsmentioning
confidence: 99%